A framework for modelling structural association amongst barriers to software outsourcing partnership formation: An interpretive structural modelling approach. Issue 6 (13th January 2020) - Ali, Sikandar; Huang, Jiwei; Khan, Siffat Ullah; Li, Hongqi
Abstract: Software Outsourcing Partnership (SOP) is considered as a type of risk and reward sharing relationship between a client organisation, in the developed countries, and its overseas vendor organisation. Regardless of numerous benefits, the development of SOP still remnants in its infancy stage due to several interactive barriers. Some studies have been conducted to examine the barriers to SOP formation. However, no attempt has been reported so far to explore the multifaceted interrelationships amongst them. To bridge the gap, this study implements Interpretive Structural Model (ISM) approach to reconnoitre the interrelationships amongst the barriers in the context of SOP formation. The objective of this research paper is to develop a framework for modelling structural association amongst the barriers. To achieve the objective, we used a hybrid methodology based on systematic literature review (SLR), empirical survey, and ISM. Firstly, via SLR study, we identified 27 barriers to SOP formation. Secondly, to empirically explore the interrelationships amongst the identified barriers, a questionnaire survey was performed with 50 experts from a total of 20 different countries. Further, interrelationships amongst the barriers were identified using ISM via panel review, and their classifications were carried out via Cross‐Impact Matrix Multiplication Applied to the Classification Approach. Abstract : In the above figure, level shows priority such that level 1 represents high priority and while level 10 shows lower priority. The barriers with the high dependence and low driving power are put at the top. Dependent barriers can be achieved by driving barriers. Top lever barrier(s) are achieved by all others but it cannot achieve any barriers except at the same level if any